Penerapan mirror therapy berbasis keluarga pada pasien CKD yang menjalani hemodialisis: Studi kasus - Putri, Intan; Arofiati, Fitri (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2025)
Background: Chronic Kidney Disease (CKD) is a decline in kidney function that often leads to muscle weakness and decreased mobility. Mirror therapy is a non-invasive rehabilitative intervention that utilizes the mirror neuron system to improve motor function. Purpose: To analyze the implementation of family-based mirror therapy in CKD patients on hemodialysis, based on the principles of nursing ethics and nursing law. Method: A case study was conducted on Mr. S, a 62-year-old patient with CKD undergoing hemodialysis. Mirror therapy was implemented at home, guided by a booklet and educational videos for the patient and family. Data were collected through clinical assessment and interviews with the patient and family. The application of ethical principles (autonomy, beneficence, non-maleficence, and justice) and compliance with Law No. 38 of 2014 and Minister of Health Regulation No. 26 of 2019 were also evaluated. Results: Mr. S, a 62-year-old male with chronic kidney disease (CKD) undergoing hemodialysis, experienced muscle weakness, fatigue, and decreased ability to perform daily activities, with a hemoglobin level of 7.9 g/dL. His family did not understand appropriate rehabilitation strategies, so the patient often rested completely or refused assistance. The implementation of family-based mirror therapy, through educational booklets and videos, facilitated safe light exercise, increased family understanding, and ensured that interventions adhered to ethical principles. Conclusion: The implementation of family-based mirror therapy has been shown to improve the patient's muscle strength, mobility, and independence.   Keywords: CKD; Ethical Principles; Family; Mirror Therapy; Nursing Law.   Pendahuluan: Chronic Kidney Disease (CKD) merupakan penurunan fungsi ginjal yang sering menyebabkan kelemahan otot serta penurunan mobilitas. Mirror therapy adalah intervensi rehabilitatif non-invasif yang memanfaatkan sistem neuron cermin untuk meningkatkan fungsi motorik. Tujuan: Untuk menganalisis penerapan mirror therapy berbasis keluarga pada pasien CKD hemodialisa, berdasarkan prinsip etik keperawatan dan hukum keperawatan. Metode: Penelitian studi kasus pada Tn. S sebagai subjek berusia 62 tahun dengan CKD yang menjalani hemodialisis. Mirror therapy diterapkan di rumah dengan panduan booklet dan video edukatif bagi pasien dan keluarga. Data dikumpulkan melalui pengkajian klinis serta wawancara dengan pasien dan keluarga. Penerapan prinsip etik (autonomy, beneficence, non-maleficence, dan justice) serta kesesuaian dengan UU No. 38 Tahun 2014 dan Permenkes No. 26 Tahun 2019 juga dievaluasi. Hasil: Tn. S berjenis kelamin laki-laki berusia 62 tahun dengan CKD yang menjalani hemodialisis, mengalami kelemahan otot, mudah lelah, dan penurunan kemampuan beraktivitas sehari-hari dengan kadar hemoglobin 7.9 g/dL. Keluarga belum memahami strategi rehabilitatif yang tepat, sehingga pasien sering beristirahat total atau menolak bantuan. Penerapan mirror therapy berbasis keluarga, melalui edukasi booklet dan video, membantu latihan ringan yang aman, meningkatkan pemahaman keluarga, dan memastikan intervensi sesuai prinsip etik. Simpulan: Penerapan mirror therapy berbasis keluarga terbukti meningkatkan kekuatan otot, mobilitas, dan kemandirian pasien.   Kata Kunci: CKD; Keluarga; Hukum Keperawatan; Mirror Therapy; Prinsip Etik.